Allium goumenissanum a new autumnal species of Allium sect. Codonoprasum (Amaryllidaceae) from north Greece - Ioannidis, Vasilis; Tzanoudakis, Dimitris (Phytotaxa, 2022)
Allium goumenisannum from the north continental Greece (NC) is described and illustrated as a species new to science. It is an autumn-flowering species classified to Allium sect. Codonoprasum and is characterized by a triploid chromosome number (2n = 3x = 24), unusual for this late-flowering species group. This paper focuses on the presentation of the main morphological and karyological characters of the new species and its possible relationships with other Greek and East Mediterranean autumnal species.